DNA Methylation Levels of the TBX5 Gene Promoter Are Associated with Congenital Septal Defects in Mexican Paediatric Patients - Esbeidy García-Flores; José Manuel Rodríguez-Pérez; Verónica Marusa Borgonio-Cuadra; Gilberto Vargas-Alarcón; Juan Calderón-Colmenero; Juan Pablo Sandoval; José Antonio García-Montes; Víctor Manuel Espinoza-Gutiérrez; Juan Gerardo Reyes-García; Benny Giovanni Cazarín-Santos; Antonio Miranda-Duarte; Armando Gamboa-Domínguez; et al. (Biology, 2022)
The TBX5 gene regulates morphological changes during heart development, and it has been associated with epigenetic abnormalities observed in congenital heart defects (CHD). The aim of this research was to evaluate the association between DNA methylation levels of the TBX5 gene promoter and congenital septal defects. DNA methylation levels of six CpG sites in the TBX5 gene promoter were evaluated using pyrosequencing analysis in 35 patients with congenital septal defects and 48 controls. Average methylation levels were higher in individuals with congenital septal defects than in the controls (p < 0.004). In five CpG sites, we also found higher methylation levels in patients than in the controls (p < 0.05). High methylation levels were associated with congenital septal defects (OR = 3.91; 95% CI = 1.02–14.8; p = 0.045). The analysis of Receiver Operating Characteristic (ROC) showed that the methylation levels of the TBX5 gene could be used as a risk marker for congenital septal defects (AUC = 0.68, 95% CI = 0.56–0.80; p = 0.004). Finally, an analysis of environmental factors indicated that maternal infections increased the risk (OR = 2.90; 95% CI = 1.01–8.33; p = 0.048) of congenital septal defects. Our data suggest that a high DNA methylation of the TBX5 gene could be associated with congenital septal defects.